The Influence of Diorama Media on Students’ Critical Thinking Skills in Social Studies Learning - Salbila, Isal; Yusnaldi, Eka (Yayasan Sembilan Pemuda Indonesia, 2025)
This study examines the impact of Diorama media on fifth-grade students’ critical thinking skills in social studies at MIS Asmaul Husna. A quantitative experimental design was employed, involving 38 fifth-grade students divided equally into control and experimental groups (19 students each). Data were collected through pretest-posttest assessments to measure critical thinking skills before and after Diorama media implementation in the experimental group. Hypothesis testing revealed a statistically significant effect (sig. 2-tailed = 0.000 < 0.05), confirming that Diorama media enhances critical thinking skills. The experimental group showed marked improvement compared to the control group, leading to the acceptance of Ha (alternative hypothesis) and rejection of Ho (null hypothesis). This study pioneers the application of Diorama media in social studies education at the elementary level, demonstrating its efficacy as an innovative pedagogical tool for fostering higher-order thinking skills. Educators can adopt Diorama media to create engaging, tactile learning experiences that promote active student participation and critical analysis in social studies curricula. The findings provide empirical evidence supporting the integration of visual-spatial learning tools in elementary education, offering a replicable model for enhancing critical thinking through multisensory instruction.